2013
DOI: 10.2903/j.efsa.2013.3391
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on Flavouring Group Evaluation 12, Revision 4 (FGE.12Rev4): primary saturated or unsaturated alicyclic alcohols, aldehydes, acids and esters from chemical groups 1 and 7

Abstract: The Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids of the European Food Safety Authority was requested to evaluate 12 flavouring substances in Flavouring Group Evaluation 12, Revision 4 (FGE.12Rev4), including two additional substances, using the Procedure in Commission Regulation (EC) No 1565/2000. The present revision includes two additional flavouring substances: 12-beta-santalen-14-ol [FLno: 02.216] and 12-alpha-santalen-14-ol ]. None of the substances was considered to have geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In agreement, the FDA considers β-ionone to be Generally Recognized as a Safe (GRAS, 21 CFR 172.515) chemical for its intended use in food. It is also included in the list of flavorings authorized by the EU according to the evaluation carried out by EFSA [133]. Regarding use in feed, β-ionone is considered safe at the normal use level (5 mg/kg complete feed) for salmonids, veal calves and dogs, whereas for the remaining target species, the use level of 1 mg/kg complete feed is considered safe [134].…”
Section: β-Ionone and β-Cyclocitralmentioning
confidence: 99%
See 2 more Smart Citations
“…In agreement, the FDA considers β-ionone to be Generally Recognized as a Safe (GRAS, 21 CFR 172.515) chemical for its intended use in food. It is also included in the list of flavorings authorized by the EU according to the evaluation carried out by EFSA [133]. Regarding use in feed, β-ionone is considered safe at the normal use level (5 mg/kg complete feed) for salmonids, veal calves and dogs, whereas for the remaining target species, the use level of 1 mg/kg complete feed is considered safe [134].…”
Section: β-Ionone and β-Cyclocitralmentioning
confidence: 99%
“…However, it should be considered that the CLP classification is exclusively hazard-based and that no other information about risks is available, especially after repeated exposure. Isocyclocitral is also included in the list of flavorings authorized by the EU, according to the evaluation carried out by the EFSA [133], in which it is reported that, based on chemical structure, the compound is expected to be oxidized to the corresponding carboxylic acid, conjugated with glucuronic acid and excreted as urinary metabolites. Since apart from an acute toxicity study, cited in the ECHA dossier as grey literature but not available (Registration Dossier-ECHA (europa.eu)), no further data have been produced.…”
Section: β-Ionone and β-Cyclocitralmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotoxicity studies -text taken 9 from EFSA FGE.12Rev4 (EFSA CEF Panel, 2013c) Data are available for the supporting substance 2,6-dimethyl-2,5,7-octatriene-1-ol acetate ], but no studies on genotoxicity are available for the 12 candidate substances. The genotoxic potential of the remaining flavouring substances cannot be fully assessed as the data are limited.…”
Section: 2mentioning
confidence: 99%